Dramska ironija v miraklu in moraliteti - Žakelj, Špela (Primerjalna književnost, 2006)
Dramatic Irony in Middle Age Miracle and Morality Play. Dramatic irony is not limited by historical period or particular literary genre, therefore it can also be found in medieval drama, which focuses mainly on moral principles based on religious beliefs. With the progressive secularisation of original liturgical drama, ironic elements are slowly introduced into performances. These elements can be observed either as interruptions of the stage illusion in prologues and epilogues, or as situational and verbal irony within the dramatic action itself.
Keywords: srednjeveška dramatika; liturgična drama; morakel; moraliteta; ironija